(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rante H, Alam G, Usmar, Zahra S, Kurniawati A, Ali A. 2022. Antimicrobial activity of Streptomyces spp. sponge-associated isolated from Samalona Island of South Sulawesi, Indonesia. Biodiversitas 23: 1392-1398. The resistance case of infectious diseases increases annually, while the necessity of antibiotics as a drug choice for therapy most important is needed. One of the efforts to overcome these problems is an investigation of new antibiotic sources, namely marine organisms. Actinomycetes are microbes well known as more antibiotic-producing than fungi and bacteria. This study aims to the identification of marine actinomycetes isolated from sponge samples in Samalona Island, South Sulawesi, Indonesia. The antimicrobial activity was evaluated against multi-drug resistant (MDR) Staphylococcus aureus, Escherichia coli, and Candida albicans. Isolation was carried out using SCA (Starch Casein Agar) medium by the pour plate method. The selected isolates were designated as SML10h and SML10a. The isolates SML 10h and SML 10a were recovered from sponges Haliclona sp. and Aplysina sp., respectively. The production of antimicrobial substances was performed by fermentation of isolates in SNB (Starch Nitrate Broth) medium for 14 days. The antimicrobial activity was shown by the ethyl acetate extract with 2 mg/20 ?L concentration against all test microbes. Phylogenetic analysis of the 16S rRNA gene sequences revealed that the similarity of SML 10a was most closely related to Streptomyces geysiriensis (98%).